Mitos e identidades nos filmes justiça vermelha, turistas e gran torino - Scafuto, Isabel Cristina (2011)
This study mainly intends to analyze the ideological, mythological and identitary aspects of the Americans. It verifies how the contemporary American mythology is adapting itself to the historical transformations it has been passing through as well, generated by one more global crises. Besides, it also considers Hollywood movies as mythological narratives. Three Hollywood films have been selected for this study: Red Corner (1995), Turistas (2006) and Gran Torino (2008). They were used as basis to the purposed analysis. In this way, the focus here is on the representation of the American citizen in each film, his speech, his relationship with the Other (the non-American), in the three different situations presented in this study